Nuovi concittadini? I giovani di origine immigrata, vettore di cambiamento della società italiana (Altre Modernità, 2009)
The article deals with the increase of a population of immigrant origins' youth in Italy, starting from  a piece of research, conducted by different methods:1-     a survey on  families whose members have been separated during the migration and now they are rejoined 2-     a survey on pre-adolescents (11-14 years old)3-     a survey on educational outcomes in secondary school4-     a survey on the opinion of immigrant origins' youth about citizenshipThe scenario outlined, where a youth population of foreign origins becomes more an more visible, questions the social and political institutions, and compels to rethink the concepts of Italian society and Italian cultural identity.
Keywords: migrazioni; seconde generazioni; giovani; famiglie; scuola; cittadinanza